2016
DOI: 10.1063/1.4950771
|View full text |Cite
|
Sign up to set email alerts
|

3D numerical modeling of the carrier transport and radiative efficiency for InGaN/GaN light emitting diodes with V-shaped pits

Abstract: In this paper, influence of a V-pit embedded inside the multiple quantum wells (MQWs) LED was studied. A fully three-dimensional stress-strain solver and Poisson-drift-diffusion solver are employed to study the current path, where the quantum efficiency and turn-on voltage will be discussed. Our results show that the hole current is not only from top into lateral quantum wells (QWs) but flowing through shallow sidewall QWs and then injecting into the deeper lateral QWs in V-pit structures, where the V-pit geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 36 publications
(39 reference statements)
3
34
0
Order By: Relevance
“…52 two blue LEDs, a high-efficiency one with V f =2.89 V at 10 A.cm −2 and a high-power one with V f =3.10 V at 35 A.cm −2 , both values being in good agreement with the I-V characteristic predicted by the 1/u-Poisson-DD model. The remaining difference could be attributed to leakage paths via V-pit structures or dislocation lines, 53 to the absence in our modeling of tunneling in perpendicular transport, or to the internal temperature of real LED devices being higher than 300 K, leading to a lower V f .…”
Section: Electrical and Optical Properties Calculated From The Locmentioning
confidence: 93%
“…52 two blue LEDs, a high-efficiency one with V f =2.89 V at 10 A.cm −2 and a high-power one with V f =3.10 V at 35 A.cm −2 , both values being in good agreement with the I-V characteristic predicted by the 1/u-Poisson-DD model. The remaining difference could be attributed to leakage paths via V-pit structures or dislocation lines, 53 to the absence in our modeling of tunneling in perpendicular transport, or to the internal temperature of real LED devices being higher than 300 K, leading to a lower V f .…”
Section: Electrical and Optical Properties Calculated From The Locmentioning
confidence: 93%
“…We setup the material parameters according to the indium map and assume that the electron and holes are generated by the absorption of optical excitation. Finally, the Poisson and drift-diffusion equations were solved self-consistently to obtain the in-plane carrier diffusion and radiative recombination distribution3536. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicated that GaN LEDs with optimized V-shaped pits under the proper growth condition of prestrained layers and less light absorption layers would provide a high-output power emission. The V f of samples A/B/C with large V-pits was lower than that of samples D/E/F with small V-pits because large V-pits facilitated a conducting path for carrier injection to MQWs [43]. In addition, samples with thicker n-type GaN layers exhibited lower V f because of the lower resistance in the thick n-type GaN layer.…”
Section: Optical and Electrical Properties Of Led Chips By El Measurementioning
confidence: 90%